The usage of conceptual metaphor in Eliot's The Waste Land and Al Sayyab's the rain song: comparative study - Ayassrah, Mohamed Ayed
There is an evident gap in investigating metaphor a a cross-cultural phenomenon in modem poetry comparatively between Arabic and English. Also, several scholars argue that further experimental studies are needed on metaphors in poetry. Moreover, it is noticed that most previous studies are about studying metaphor in and for English language so that there is a manifest inadequacy in the previous as well as current studies in inve tigating the usages of the conceptual metaphor comparatively among different languag s. This study aimed to contrast and compare modern Arabic to English po try in using the conceptual metaphor. Unquestionably, the best choic s to be the cope of the study were T.S Eliot and Al Sayyab due to their vital roles in establishing the base of modern poetry in their languages. This study adopted Conceptual Metaphor Theory to shed light on using the conceptual metaphor in modern Arabic versus English poetry comparatively. It concentrated on the usage of conceptual metaphor in AI Sayyab's Rain Song and T. S. Eliot's Waste Land as two poles of modernism movement. All conceptual metaphors of the two poems were extracted, studied, analysed and finally classified into juxtaposed tables according to the suitable domain of their central concepts in order to meet the aims of the study. The stud u ed four different strategies to analyse the data comparatively; these strategies were the 'Up and Down', 'Personification', Animate and Inanimate', and 'Five Source Domain'. The final result showed that conceptual metaphor played a vital role in distinguishing the language of modern poetry. Also, the two poems were pessimistic and metaphoric. The Rain Song involved conceptual metaphors in a portion of 65 % of the total lines, while The Waste Land had only 39 %; this indicated that The Rain ong dramatically exceeded The Waste Land in using this phenomenon. It was also revealed that The Rain Song surpassed The Waste Land in six domains, but The Waste Land exceeded only in four. In spite of the various dissimilarities between the two poems in many aspects, several expressions, symbols, themes and styles were shared by the two poems. Finally, this study uncover that many aspects ofintertextuality went from The Waste Land to The Rain Song. This study was the first that purported to investigate the usages of conceptual metaphor between The Rain Song and The Waste Land comparatively. So, it helped in declaring the importance of this phenomenon in both modern Arabic and English poetry. Furthermore, it elucidated the role of metaphor in breaking the codes of the two poems and so helping in illustrating and interpreting the implicit poetic scenes. Moreover, it paved the way for future researches to study this phenomenon between modern Arabic and English comparatively. Finally, it contributed to the previous studies via collecting, analysing and presenting some data about the conceptual metaphor, its usage and its pragmatic functions in Arabic and English trying to treat part of lacking related studies.